VD_FINDINFO Jug / 2025 / 106 vom 4. Oktober 2024 - VD Tribunal cantonal (2024)
ACTE D'ORDRE SEXUEL, PEINE PRIVATIVE DE LIBERTÉ, LÉSION CORPORELLE SIMPLE | 189 CP, 10 CPP (CH), 398 al. 3 let. b CPP (CH)